Analysis of Hydroquinone in Face Whitening Cream by UV-Vis Spectrophotometry and GC-MS Spectrometry - Karnelasatri, Karnelasatri; Tahya, Candra Yulius; Adila, Mahda Uli; Hardy, Junius; Munthe, Sri Wahyu Ningsih (Indonesian Journal of Chemical Research, 2024)
The analytical method to determine the compound content in both food and cosmetic products must be carried out carefully to ensure the validity of the analysis results. Hydroquinone has been widely found to be used as an active whitening agent in whitening cream. Technological advances have led to illegal whitening creams becoming more accessible online. This study aims to examine the hydroquinone content in the whitening samples cream purchased from e-commerce by various analytical methods, such as FeCl3 reagent, cerimetric titration, UV-Vis spectrophotometry, and GC-MS spectrometer compared to the positive control hydroquinone. The results of the hydroquinone content by cerimetric titration and UV-Vis spectrophotometry methods were calculated quantitatively. Furthermore, the result compared through statistical tests showed a consistent hydroquinone content for both methods. Contrariwise, the GC-MS method showed negative results due to differences in the extraction process and solvent solubility. Based on the result obtained, can be concluded that all samples of whitening cream did not meet the requirements of BPOM No. 23 of 2019.